2019
DOI: 10.1016/j.biocon.2019.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal competencies define effective conservation leadership

Abstract: Effective leadership is considered essential for conservation success, but there is currently not enough understanding of what conservation leaders are doing, and what they should be doing, in order to be effective. Other sectors, such as health, commerce, education, industry and the military have studied leadership for decades, and have a good knowledge of particular styles and suitable instruments for measuring leadership effectiveness. This study uses the perspectives of conservation professionals through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 71 publications
3
25
0
Order By: Relevance
“…Visioning is an acquired skill, yet training has limited effect (Frese, Beimel, & Schoenborn, 2003) and little impact on other leadership skills. Creating an inspirational vision was considered among the most important leadership competencies on two surveys of conservation professionals (Bruyere, 2015;Englefield et al, 2019). Straka et al (2018) emphasise the need to engage others including wider stakeholders in vision building in order to make this relevant.…”
Section: Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visioning is an acquired skill, yet training has limited effect (Frese, Beimel, & Schoenborn, 2003) and little impact on other leadership skills. Creating an inspirational vision was considered among the most important leadership competencies on two surveys of conservation professionals (Bruyere, 2015;Englefield et al, 2019). Straka et al (2018) emphasise the need to engage others including wider stakeholders in vision building in order to make this relevant.…”
Section: Visionmentioning
confidence: 99%
“…Recently Englefield et al (2019) identified that many important leadership skills are still rarely encountered in the behaviour and actions of conservation leaders, including vision, building trust and enabling others. These studies illustrate the breadth of topics relevant to this review which still need to be better understood in the context of modern psychological knowledge of leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal competencies specifically include possessing the necessary human qualities, knowledge, abilities and skills related to processes and interpersonal relationships in teaching, possessing the ability to create trust and empathy towards colleagues and other individuals, creating positive interdependence and equal participation in work, ability to act by personal example with expressed propensity for individual and group responsibility (Englefield et al, 2019;Brundiers and Wiek, 2017;Gojkov, 2012). Certain authors (Jurčić, 2014;Vrkić-Dimić, 2013;Andevski and Arsenijević, 2012), see necessary for functioning in a system of digital education that is constantly changing and transforming.…”
Section: Introductionmentioning
confidence: 99%
“…Such an endeavour requires the identification and wide recognition of the competences required to deliver effective threatened species recovery (Englefield et al, 2019). Such recognition demonstrates that ensuring the future of the planet's biodiversity and life support systems is a complex, multi-skilled profession worthy of respect, recognition and support (Appleton, 2016).…”
Section: Origins Of the Projectmentioning
confidence: 99%